Analysis of the method of teaching structures in the Arabic language teaching book of the Ministry of Religious Affairs - Ismail, Taufik; Syukron, Hanif (JURNAL IJ-ATL, 2023)
The Indonesian Ministry of Religious Affairs has extracted a new book on teaching the Arabic language and also applies the new teaching curriculum. This research aims at two important things: First, to analyze the curriculum for teaching grammatical structures in the Arabic language teaching book for the first secondary grade of the Indonesian Ministry of Religious Affairs in 2020. Second, to evaluate it in light of the book Idhaat for teachers of Arabic for non-native speakers. This research uses the qualitative and quantitative analysis method with the use of symbols N=fx/nx6 x100%, the data analysis method used by the researcher is the Miles and Huberman method. As for the results of this research, there are two things: 1.) It focuses and is completed on four elements of the Arabic language teaching curriculum after observation and tracking. 2.) That the study of structures in it after its evaluation in light of the Idhaat book is very suitable for teaching it, as it is at the rate of standards in the Idhaat book of 87%, meaning that it is very suitable and the curriculum is suitable for teaching it at this stage after tracking and observation.